Antinociceptive activity of methanol extract of Chlorophytum alismifolium tubers in murine model of pain: Possible involvement of a2-adrenergic receptor and KATP channels - Abubakar, Abdulhakim; Balarabe Nazifi, Abdullahi; Odoma, Saidi; Shehu, Salisu; Danjuma, Nuhu Mohammed (Journal of Traditional and Complementary Medicine, 2020)
The tubers of Chlorophytum alismifolium are used in Nigerian Herbal Medicine for the management of diabetes mellitus, painful and inflammatory conditions. The antinociceptive activity has been validated but the mechanism of this activity is yet to be explored. This study therefore, aimed to investigate the probable mechanism(s) of the antinociceptive activity of C. alismifolium tubers using experimental animal model of pain. HPLC and GC-MS analyses were carried out on the extract. Antinociceptive activity was investigated using acetic acid-induced writhing response test in mice. Three groups of mice were orally administered distilled water (10ml/kg), C. alismifolium (400 mg/kg) and morphine (10 mg/kg) 60 min before administration of acetic acid and the resulting writhing were counted for 10 min. To establish the probable mechanism(s) of action of C. alismifolium, separate groups of animals were pretreated intraperitoneally with naloxone (2 mg/kg), prazosin (1 mg/kg), yohimbine (1 mg/kg), propranolol (20 mg/kg) and glibenclamide (5 mg/kg) 15 min before C. alismifolium administration. HPLC chromatogram of the extract revealed seventeen characteristic peaks with retention times ranging between 2.1 and 7.4min. Administration of C. alismifolium significantly (p < 0.01) reduced the mean number of writhes compared to control group. Pretreatment with yohimbine and glibenclamide significantly (p < 0.05 and p < 0.01 respectively) reduced the antinociceptive activity of extract-alone treated group. However, pretreatment with prazosin, naloxone and propranolol showed no effect on its analgesic activity. The findings from this research revealed the possible involvement of a2-adrenergic receptor and KATP channels in the antinociceptive activity of Chlorophytum alismifolium tuber extract.
Keywords: Chlorophytum alismifolium; Antinociception; Pain mechanism; Adrenergic; KATP Channels